2021
DOI: 10.1186/s12951-021-00857-w
|View full text |Cite
|
Sign up to set email alerts
|

Glycol chitosan-based tacrolimus-loaded nanomicelle therapy ameliorates lupus nephritis

Abstract: Background Recently, we developed hydrophobically modified glycol chitosan (HGC) nanomicelles loaded with tacrolimus (TAC) (HGC-TAC) for the targeted renal delivery of TAC. Herein, we determined whether the administration of the HGC-TAC nanomicelles decreases kidney injury in a model of lupus nephritis. Lupus-prone female MRL/lpr mice were randomly assigned into three groups that received intravenous administration of either vehicle control, an equivalent dose of TAC, or HGC-TAC (0.5 mg/kg TAC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Additionally, it improved renal function, decreased tissue injury and fibrosis, and reduced renal oxidative damage and inflammation, which were associated with inhibiting the NF-ƙB signaling pathway ( Hassan et al, 2021 ). In a classical model of lupus nephritis, the administration of MRL/lpr, which are hydrophobically modified glycol chitosan nanomicelles loaded with tacrolimus, decreased glomerulosclerosis and suppressed intrarenal inflammation via the NF-ƙB signaling pathway ( Kim et al, 2021 ). Suo et al (2021) reported that bortezomib improved renal allograft tubulointerstitial fibrosis by inhibiting the NF-ƙB-TNF-α-Akt-mTOR-P70S6K-Smurf2 pathway via IƙBα protein stabilization.…”
Section: Therapeutic Strategies Targeting the Nf-ƙb Signaling Pathway...mentioning
confidence: 99%
“…Additionally, it improved renal function, decreased tissue injury and fibrosis, and reduced renal oxidative damage and inflammation, which were associated with inhibiting the NF-ƙB signaling pathway ( Hassan et al, 2021 ). In a classical model of lupus nephritis, the administration of MRL/lpr, which are hydrophobically modified glycol chitosan nanomicelles loaded with tacrolimus, decreased glomerulosclerosis and suppressed intrarenal inflammation via the NF-ƙB signaling pathway ( Kim et al, 2021 ). Suo et al (2021) reported that bortezomib improved renal allograft tubulointerstitial fibrosis by inhibiting the NF-ƙB-TNF-α-Akt-mTOR-P70S6K-Smurf2 pathway via IƙBα protein stabilization.…”
Section: Therapeutic Strategies Targeting the Nf-ƙb Signaling Pathway...mentioning
confidence: 99%
“…Treatment with a combination of short and low doses of them can attenuate the systemic symptoms in collagen-induced arthritis mice, driven by the downregulation of T helper cells (Th) 17 bc2-specific antigenic responses and enhancement of Th2-type T cell responses (Mangal et al, 2022). Meanwhile, chitosan NPs have also yielded noteworthy 2020), Kim et al (2021) Nrf2, nuclear factor E2-related factor 2; Keap 1, kelch-like ECH, associated protein 1; ARE, antioxidant response element; RXRα, retinoic X receptor α; Cul3, cullin-based E3 ligase; RBX1, ring box protein 1; sMaf, small Maf proteins; AREs, antioxidant response elements; EpRE, electrophile response element; β-TrCP, beta-transducin repeats-containing protein; NPs, nanoparticles; p38 MAPK, mitogen-activated protein kinase p38 antibody; TRAF2, tumor necrosis factor receptor-associated factor 2; MKK3, p38 MAPK, kinase 3; ATF-2, activating transcription factor 2; HSP27, heat shock protein 27; MAPKAPK, MAPK-activated protein kinase; MNK, MAPK, signaling integrated kinase; JAK, janus kinase; STAT3, signal transducers and activators of transcription 3; G-CSF, granulocyte colony-stimulating factor; EPO, erythropoietin; TPO, thrombopoietin; EGFR, epidermal growth factor receptor; NF-κB, nuclear factor κB; Rel, REL, protooncogene; IκBα, inhibitor kappa B alpha; TNFR, tumor necrosis factor receptor; IL, interleukin; TNF-α, tumor necrosis factor-alpha; TLR, toll-like receptor; TIR, toll-interleukin 1 receptor; Myd88, myeloid differentiation primary response protein 88; TIRAP, TIR, domain-containing adapter protein; IRAK, IL-1, receptor-associated kinase; TRAF6, TNF, receptor associated factor 6; PI3K, phosphatidylinositol-3-kinase; AKT, serine/threonine kinase; PIP2, phosphatidylinositol-4, 5-bisphosphate; PDK1, 3-phosphoinositide-dependent protein kinase 1; TSC, tuberous sclerosis complex; PTEN, protein tyrosine phosphatase; TGF-β, transforming growth factor beta; SMAD, drosophila mothers against decapentaplegic protein; TGF-βR, TGF-β, receptor; BMP, bone morphogenetic protein; GDF, growth differentiation factors.…”
Section: Inflammation In Rheumatoid Arthritis and Systemic Lupus Eryt...mentioning
confidence: 99%
“…CS/HA pDNA effectively alleviated fibrosis and restored renal function in unilateral ureteral obstruction (UUO) mouse models of CKD. Kim et al developed hydrophobically modified glycol chitosan (HGC) nanomicelles loaded with tacrolimus (HGC-TAC) for LN therapy. HGC-TAC nanomicelle has a diameter of 370 ± 22 nm and a positive charge of 24 ± 4 mV.…”
Section: Renal Targeted Drug Deliverymentioning
confidence: 99%
“…CS/HA pDNA effectively alleviated fibrosis and restored renal function in unilateral ureteral obstruction (UUO) mouse models of CKD. Kim et al152 developed hydrophobically…”
mentioning
confidence: 99%